2014
DOI: 10.1038/nsmb.2851
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of asymmetric polymerase assembly at the eukaryotic replication fork

Abstract: Eukaryotes use distinct polymerases for leading- and lagging-strand replication, but how they target their respective strands is uncertain. We reconstituted Saccharomyces cerevisiae replication forks and found that CMG helicase selects polymerase (Pol) ε to the exclusion of Pol δ on the leading strand. Even if Pol δ assembles on the leading strand, Pol ε rapidly replaces it. Pol δ–PCNA is distributive with CMG, in contrast to its high stability on primed ssDNA. Hence CMG will not stabilize Pol δ, instead leavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
292
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(316 citation statements)
references
References 58 publications
21
292
2
1
Order By: Relevance
“…Omitting RFC-Δ1n or PCNA did not reduce repair in contrast to the previously observed complete dependence of Pol δ-dependent repair on RFC-Δ1n or PCNA (25). This result is consistent with prior observations that extensive DNA synthesis by Pol δ requires PCNA and its loading factor RFC, whereas extensive DNA synthesis by Pol e is not absolutely dependent on PCNA or RFC (54). Finally, omitting RPA did not reduce the amount of repair observed.…”
Section: Resultscontrasting
confidence: 37%
See 2 more Smart Citations
“…Omitting RFC-Δ1n or PCNA did not reduce repair in contrast to the previously observed complete dependence of Pol δ-dependent repair on RFC-Δ1n or PCNA (25). This result is consistent with prior observations that extensive DNA synthesis by Pol δ requires PCNA and its loading factor RFC, whereas extensive DNA synthesis by Pol e is not absolutely dependent on PCNA or RFC (54). Finally, omitting RPA did not reduce the amount of repair observed.…”
Section: Resultscontrasting
confidence: 37%
“…DNA replication is a highly coordinated process with leadingstrand DNA synthesis being performed by Pol e coupled to the cell division cycle 45 (Cdc45)/mini-chromosome maintenance proteins 2-7 (Mem2-7)/Sld5-Psf1-3 (GINS) DNA helicase complex (also called the CMG complex), and other proteins, and lagging-strand DNA synthesis primarily being performed by Pol δ and its accessory factor PCNA following initiation of laggingstrand synthesis by DNA Pol α/primase (52,54). MMR appears to be coupled to the replication fork as evidenced by the timing of MMR and the colocalization of the Msh2-Msh6 mispair recognition complex with replication fork proteins during S phase (55,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, if there were an interaction between CMG and Pol δ, the affinity would be at least 3 orders of magnitude weaker than the interaction between CMG and Pol e. Therefore, CMG does not bind and stabilize Pol δ-PCNA. We therefore propose that Pol δ-PCNA undergoes collision release upon the encounter with CMG, accounting for the observed slow and distributive action of Pol δ-PCNA on the leading strand (9).…”
Section: Quality Control Of Polmentioning
confidence: 99%
“…The replication protein A (RPA) heterotrimer binds and protects the single-strand (ss) DNA of the lagging strand against nucleases, and helps melt secondary structure in ssDNA. Reconstitution of the core eukaryotic replisome using all three replicative DNA polymerases has recently been accomplished with pure recombinant proteins in the S. cerevisiae system (9)(10)(11). These in vitro studies revealed that Pol e binds directly to CMG, forming a CMGE complex (a complex of CMG bound to Pol epsilon), and this recruits Pol e to PCNA on the leading strand for efficient extension.…”
mentioning
confidence: 99%